2017
DOI: 10.1016/j.neo.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells as Precursors for Osteoblasts in the Metastatic Prostate Cancer Bone

Abstract: Prostate cancer cells metastasize to the bones, causing ectopic bone formation, which results in fractures and pain. The cellular mechanisms underlying new bone production are unknown. In a recent study, Lin and colleagues, by using state-of-the-art techniques, including prostate cancer mouse models in combination with sophisticated in vivo lineage-tracing technologies, revealed that endothelial cells form osteoblasts induced by prostate cancer metastasis in the bone. Strikingly, genetic deletion of osteorix p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…De La Fuente and colleagues show that in vitro and ex vivo pericyte‐derived Lama2 mediate oligodendrocyte progenitor differentiation. Transgenic mice have been widely applied to study distinct cell types within tissues microenvironments (Andreotti, Lousado, Magno, & Birbrair, ; Azevedo et al, ; Birbrair, ; Birbrair & Frenette, ; Borges et al, ; Paiva et al, ). The ability, not only to ablate cells, but also to delete single genes in specific cellular populations in adult mice has allowed us to answer specific questions regarding the roles of different cell subsets in the regulation of several physiologic processes.…”
Section: Perspectives/future Directionsmentioning
confidence: 99%
“…De La Fuente and colleagues show that in vitro and ex vivo pericyte‐derived Lama2 mediate oligodendrocyte progenitor differentiation. Transgenic mice have been widely applied to study distinct cell types within tissues microenvironments (Andreotti, Lousado, Magno, & Birbrair, ; Azevedo et al, ; Birbrair, ; Birbrair & Frenette, ; Borges et al, ; Paiva et al, ). The ability, not only to ablate cells, but also to delete single genes in specific cellular populations in adult mice has allowed us to answer specific questions regarding the roles of different cell subsets in the regulation of several physiologic processes.…”
Section: Perspectives/future Directionsmentioning
confidence: 99%
“…The hematopoietic stem cells, which give rise to all blood and immune cells throughout life, reside in a specific complex niche in the bone marrow, that supports the homeostasis of these cells, composed by osteoblasts, osteocytes, osteoclasts, endothelial cells, adipocytes, smooth muscle cells, pericytes, fibroblasts, macrophages, megakaryocytes, lymphocytes, hematopoietic progenitors, neutrophils, peripheral innervations, and Schwann cells [18,85,64,8689,19,9,10,90,93]. Recent studies have revealed distinct contributions of several cellular components of the bone marrow to different functions of hematopoietic stem cells regulation.…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%
“…The use of transgenic mouse models in which specific cell types can be genetically ablated has proved valuable for understanding the role of specific cell types in physiological and pathological states [4854]. O'Farrell and colleagues place pericytes as central responsibles in cardiac vasoconstriction [9].…”
Section: Perspectives/future Directionsmentioning
confidence: 99%